Transformasi Kompetensi Pedagogik Guru di Era Kecerdasan Artifisial Tinjauan Literatur - Dariyono Dariyono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Abstract. The rapid advancement of Artificial Intelligence (AI) has significantly transformed the educational landscape, including changes in teachers’ pedagogical competencies. This study aims to examine the development of research on the transformation of teachers’ pedagogical competencies in the context of AI utilization, identify the pedagogical competency components that have undergone transformation, and analyze the opportunities, challenges, and future directions of competency development in the digital era. The study employed a literature review method with a descriptive qualitative approach. Data were collected from 11 international scholarly articles focusing on Education 4.0, teachers’ digital competence, educational transformation, 21st-century skills, sustainable education, and inclusive education. Data analysis was conducted through identification, classification, reduction, and thematic synthesis of findings from the selected literature. The results indicate that the transformation of teachers’ pedagogical competencies is characterized by an increasing need for digital literacy, technology integration skills, adaptability to change, critical thinking, creativity, collaboration, communication, and lifelong learning. Furthermore, the role of teachers has shifted from information transmitters to facilitators, mentors, and managers of digital learning environments. The study concludes that the transformation of pedagogical competencies represents a response to technological advancements and the demands of Education 4.0, requiring the strengthening of digital competencies and 21st-century skills as essential foundations for teachers’ professionalism in the future.Keywords: pedagogical competence, artificial intelligence, Education 4.0, teachers’ digital competence, educational transformation, literature review